2020
DOI: 10.1002/adma.202000074
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Approach to Aqueous Energy Storage via Ultralow‐Cost Electrolyte with Super‐Concentrated Sugar as Hydrogen‐Bond‐Regulated Solute

Abstract: Compared with the organic, ionic liquid, and solid-state electrolytes, aqueous electrolytes have the advantages of good security, environmental friendliness, high ionic conductivity, low cost, and high operability in ordinary environments. [1][2][3][4][5] Therefore, aqueous secondary ion batteries/capacitors are more attractive in large-scale energy storage, and have greater application prospects. [6][7][8][9] However, even so, there still exists several disadvantages as follows: 1) The thermodynamic electroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(58 citation statements)
references
References 34 publications
0
55
0
Order By: Relevance
“…The seawater-based electrolyte (2 M ZnSO 4 in seawater) has a wider electrochemical window increased from 2.4 V to 2.6 V as compared with DI water-based electrolyte (2 M ZnSO 4 in DI water). When using seawater as a solvent, the content of free water molecules decreases, which has been proven to be an effective strategy to expand the electrochemical stability window 21 , 40 . Moreover, the Zn 3 Mn electrode shows a significantly improved anti-corrosion ability in the seawater-based electrolyte as compared to the Zn electrode (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The seawater-based electrolyte (2 M ZnSO 4 in seawater) has a wider electrochemical window increased from 2.4 V to 2.6 V as compared with DI water-based electrolyte (2 M ZnSO 4 in DI water). When using seawater as a solvent, the content of free water molecules decreases, which has been proven to be an effective strategy to expand the electrochemical stability window 21 , 40 . Moreover, the Zn 3 Mn electrode shows a significantly improved anti-corrosion ability in the seawater-based electrolyte as compared to the Zn electrode (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the organic components of the hybrid electrolytes can be extended to macromolecules. Recently, Xue et al [203] reported that the mixture of lowcost hydroxyl-rich sugar and water can act as a solvent to dissolve metal salts. The resultant electrolyte exhibits high ESW (2.8 V on Pt electrodes), moderate ionic conductivity (8 mS cm −1 ), and wide applicable temperature range (-50 to 80°C).…”
Section: Aqueous and Hybrid Electrolytesmentioning
confidence: 99%
“…These data are summarized from the following references: 21 m LiTFSI, [2] 30 m ZnCl 2 , [41] 17 m NaClO 4 , [25] 22 m LiNO 3 , [35] 12 m NaNO 3 , [26] 25 m NH 4 CH 3 COO, [15] 22 m KCF 3 SO 3 , [79] 21 m LiTFSI + 7 m LiOTF, [16] 32 m KOAc + 8 m LiOAc, [19] 9.26 m NaCF 3 SO 3 + 1 m Na 2 SO 4 , [68] 9 m NaOTF + 22 m TEAOTF, [42] 42 m LiTFSI + 21 m Me 3 EtN•TFSI, [43] [30] 21 m LiTFSI-H 2 O/9.25 m LiTFSI-DMC (1:1), [32] [29] LiTFSI + 94%PEG + 6%H 2 O, [44] 2 M NaNO 3 + 66.7 wt% sucrose. [122] the motion of ions follows Stokes-Einstein law. [37] In contrast, the ion transport mechanism of WISEs is not consistent with the above because of the unusual solvation structure.…”
Section: Introductionmentioning
confidence: 96%